Proceedings of the 34th International Power Sources Symposium
DOI: 10.1109/ipss.1990.145866
|View full text |Cite
|
Sign up to set email alerts
|

Discharge characteristics of lithium/liquid cathode system using SO/sub 2/ based electrolyte

Abstract: Li/SO2C1, cells using SO, solvate electrolyte have been dischar ed with current demonstrate the ability of the system to operate in a wide range of temperature (-30'C densities up to 200 mA/cm. 4 The results, +7O'C) '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A recent work (5), has shown that this electrolyte was also suitable for fundamental studies of the reduction of SO2C12 because of its stability over a large range of potentials. Furthermore, using the solvate provided improvements in discharge characteristics of Li/SO2C12 cells due to the high solvate conductivity over a large range of temperatures (6).…”
mentioning
confidence: 99%
“…A recent work (5), has shown that this electrolyte was also suitable for fundamental studies of the reduction of SO2C12 because of its stability over a large range of potentials. Furthermore, using the solvate provided improvements in discharge characteristics of Li/SO2C12 cells due to the high solvate conductivity over a large range of temperatures (6).…”
mentioning
confidence: 99%